2016
DOI: 10.5603/nmr.2016.0005
|View full text |Cite
|
Sign up to set email alerts
|

Dual-time point 18FDG-PET/CT imaging may be useful in assessing local recurrent disease in high grade bone and soft tissue sarcoma

Abstract: BACKGROUND: Sarcomas comprise 1% of malignant tumors in adults but represent a significant diagnostic and therapeutic challenge. Molecular imaging with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 23 publications
0
4
0
2
Order By: Relevance
“…MATLAB was used to define and extract these features. In particular, for texture features, the package presented by Dancheva et al, 37 which is IBSI compliant, 38 was employed. These features are defined as follows.…”
Section: Supporting Informationmentioning
confidence: 99%
“…MATLAB was used to define and extract these features. In particular, for texture features, the package presented by Dancheva et al, 37 which is IBSI compliant, 38 was employed. These features are defined as follows.…”
Section: Supporting Informationmentioning
confidence: 99%
“…De même, dans une sé rie de 57 patients atteints d'une tumeur osté oarticulaire suspecte de malignité , Shen et al ont montré les limites de l'acquisition DTP (1 h-2 h) dont les performances n'é taient pas supé rieures à celles des valeurs de la TEP pré coce [162]. Dans une sé rie de 15 patients avec une suspicion de ré cidive locale de sarcome des tissus mous et des os, Dancheva et al ont montré qu'une acquisition DTP (60-120 min) de la 18 F-FDG TEP permettait d'augmenter significativement la sensibilité (100 %), la spé cificité (80 %) et la pré cision (89 %) de la technique pour les tumeurs de haut grade, mais que peu dans les tumeurs de bas grade [163]. Enfin, chez un patient aux anté cé dents d'osté osarcome de la base du crâne traité par chirurgie et chimiothé rapie, Chen et al ont montré qu'une ré cidive locale prouvé e histologiquement ne pré sentait pas de captation du 18 F-FDG sur l'acquisition pré coce alors qu'un hypermé tabolisme suspect apparaissait sur l'acquisition tardive [164].…”
Section: Lymphomesunclassified
“…Dans le cadre de lé sions des tissus mous et osté o-articulaires, les ré sultats sont à nouveau discordants d'une é tude à l'autre avec certaines ne montrant pas d'avantage de l'acquisition DTP [161,162], une montrant une amé lioration de la spé cificité mais aux dé pens de la sensibilité [160] et une derniè re montrant une amé lioration des sensibilité et spé cificité pour l'identification d'une ré cidive de sarcome des tissus mous ou osseux mais dans une petite sé rie de patients et que dans les formes de haut grade [163].…”
Section: Caracte´risation Malin/be´ninunclassified
“…When identifying the local recurrence of bone sarcoma, MRI is usually considered, whereas PET/CT serves as a complementary method. A recent study found that dual-time point F-18-FDG PET/CT has a good performance in assessing local recurrence in high grade osteosarcoma (35). Its sensitivity, specificity, and accuracy in high grade sarcomas at 120 minutes are 100%, 80%, and 89%, but only 50%, 75% and 66% in low grade sarcomas, respectively (35).…”
Section: Pet/ct In the Relapse Of Osteosarcomamentioning
confidence: 99%
“…A recent study found that dual-time point F-18-FDG PET/CT has a good performance in assessing local recurrence in high grade osteosarcoma (35). Its sensitivity, specificity, and accuracy in high grade sarcomas at 120 minutes are 100%, 80%, and 89%, but only 50%, 75% and 66% in low grade sarcomas, respectively (35). Furthermore, F-18-FDG PET/CT could detect local recurrence more than 3 years after tumor resection (36).…”
Section: Pet/ct In the Relapse Of Osteosarcomamentioning
confidence: 99%